GEOCHEMICAL AND PETROGENETIC FEATURES OF MINERALIZATION IN RARE-ELEMENT GRANITIC PEGMATITES IN THE LIGHT OF CURRENT RESEARCH - Černý P. (My University, 1992)
Tremendous expansion of high-technology applications of rare metals and specialty minerals requires periodic reassessment of their geological sources, keeping in mind the long-range technological potential of all hi-tech materials available from a given type of deposit. Granitic pegmatites are a classic example of diversified sources (Li, Rb, Cs, Be, Ga, Sc, Y, REE, Sn, Nb, Ta, U, Th, Zr, Hf; optical quartz and fluorite, high-purity feldpar, petatite and refractory spodumene, ceramic amblygonite,e tc.). Such rare-element pegmatites can be subdivided into three principal families: LCT pegmatites with Li, Rb, Cs Be, Ga, Sn, Ta > Nb (B, P, F); NYF pegmatites with Nb > Ta, Ti, Y, REE, Zr, Th, and U(F); pegmatites with a mixed geochemical signature.